Knowledge, Attitude and Practices Related to Pet Contact and Associated Zoonoses in Jammu - R. Jeelani, R. Nanda, P. Kumar, R. Raina, B. Bhushan, M. Rashid, R. K. Sharma, P. S. Mahapatra and A. W. Ganai, (Indian Journal of Extension Education, 2018)
Many zoonotic infections are transmitted through contact with animals including household pets. A pretestedquestionnaire cum interview schedule was employed to collect the data pertaining to the researchproblem from a total of randomly selected 248 respondents in order to investigate the objectives of thisstudy which were; pet keeping practices, attitude and knowledge level of pet owners regarding scientificallyadvocated pet keeping practices. The mean age of pet owners was about 36 years with a standard deviationof 12.47. Majority of the pet owners (91.5%) were male and only (8.5%) were females with a good educationaland occupational background. Majority of the respondents kept canines as pets for leisure, fed themcommercial feeds and housed them indoors. Children in the families played with pets and pet owners werevery concerned about the zoonotic transmissions. Mostly pet owners had a neutral attitude towards pets asa part of their family and the knowledge index regarding scientifically advocated pet practices was onlyabout 45 per cent.